Numerical study on electron energy distribution characteristics and evolution of active particles of methanol-air mixture by non-equilibrium plasma. (15th February 2020) - Gong, Changming; Yi, Lin; Wang, Kang; Huang, Kuo; Liu, Fenghua
Abstract: The extent of combustion enhancement by non-equilibrium plasma strongly depends on the electric field and electron number density. The electron energy distribution characteristics and evolution of active particles of methanol-air mixture by non-equilibrium plasma were numerical simulated. As an introductory work in this field, this study only partially cited other people's data for comparative verification under without experimental validation data. The results showed that the electron energy distribution is mainly affected by field intensity. The electron energy distribution is increased with the increase of mean electron energy. The field intensity directly affects the formation and development of radicals in methanol-air plasma discharge. The generation of radicals in plasma discharge mainly occurs in the electron collision reaction with the electron energy of 3–10 eV. The concentration of excited states matter is higher than that of ionized states matter. The concentration of O radical is higher than the concentration of H and CH2 OH, and then the concentration of H and CH2 OH is much than that of OH and CH3 . Considering the demand of radical concentration and economics of the peak pulse voltage, the field intensity of 220 Td - 400 Td is selected as a reasonable range for generating radicals. Highlights: Energy distribution and particles evolution of methanol-air plasma are simulated. Electron energy distribution is mainly affected by field intensity. Effect of the excess air ratio on electron energy distribution is negligible. Field intensity of 220–400 Td is a reasonable range for generating radicals. Evolution mechanism of active particles is clarified.